Evolutionary dynamics of an at‑rich satellite DNA and its contribution to karyotype differentiation in wild diploid arachis species - Samoluk, Sergio Sebastián (2016)
Fil: Samoluk, Sergio Sebastián. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.